I am Hé: creating cultural awareness in teaching Mandarin as a foreign language - Jafri, Nuraini; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
At present, the mere rise of China’s economy has made China as an emerging global superpower. The emergence of China’s economic growth has pushed the Mandarin language itself to become a global language. In fact, the Mandarin language is the new current trend with nearly a quarter of the world’s population speaks Mandarin Chinese as their native language (Hua, 2002). Hence, given the current situations and opportunities, the wide spread use of this language for non-native speakers to learn has arguably never been more important. Although it seems plausible to accept Mandarin as a foreign language, the language however could be very difficult for one to master. Mandarin language is known as one of the most difficult languages to be learned (Hong & Moreira, 2002). There are four main skills in learning Mandarin which are reading, writing, listening and speaking. According to Ellis (1999), in order for one to grasp the language comprehensively, the learner should be fully immersed within the language. The integration of cultures into the curriculum is one of the best ways to structure instruction for a more meaningful learning, which is by connecting the cultures to the learners’ lives in the real world (Hill & Mannheim, 1992; Ding & Saunders, 2006). Therefore, this concept paper discusses the role of Chinese culture as the core value in foreign language classroom as language and culture are intertwined. The cultivation of a broader cultural awareness beyond the core content knowledge is crucial among the language educators. The relationship between language teachers’ cultural awareness and pedagogical practices are inseparable. It is very vital for the teachers to understand their responsibilities and their dynamic relationship between teaching and learning in producing lifelong learners. Thus through the discussion in the paper, the authors hope to instill the idea of immersions of culture in the curriculum for the betterment of the students in learning Mandarin as a foreign language comprehensively.